2017
DOI: 10.1002/jcph.980
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Memantine on Serum Levels of Neuron‐Specific Enolase and on the Glasgow Coma Scale in Patients With Moderate Traumatic Brain Injury

Abstract: Traumatic brain injury (TBI) is a major cause of disability and death globally. Despite significant progress in neuromonitoring and neuroprotection, pharmacological interventions have failed to generate favorable results. We examined the effect of memantine on serum levels of neuron-specific enolase (NSE), a marker of neuronal damage, and the Glasgow Coma Scale (GCS) in patients with moderate TBI. Patients were randomly assigned to the control group (who received standard TBI management) and the treatment grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 42 publications
0
29
0
1
Order By: Relevance
“…Memantine (1–10 μM), when applied to rat hippocampal neurons in vitro, inhibited extrasynaptic NMDAR-induced currents while largely sparing synaptic activity [ 37 ]. In a randomized controlled trial of moderate TBI patients, enteral administration of memantine (30 mg twice daily for 7 days) post-injury resulted in substantial improvement in GCS scores at 3 days and significant reduction in neuronal damage at 7 days, as evident from reduced serum levels of neuron-specific enolase (NSE) [ 38 ].…”
Section: Excitotoxicitymentioning
confidence: 99%
“…Memantine (1–10 μM), when applied to rat hippocampal neurons in vitro, inhibited extrasynaptic NMDAR-induced currents while largely sparing synaptic activity [ 37 ]. In a randomized controlled trial of moderate TBI patients, enteral administration of memantine (30 mg twice daily for 7 days) post-injury resulted in substantial improvement in GCS scores at 3 days and significant reduction in neuronal damage at 7 days, as evident from reduced serum levels of neuron-specific enolase (NSE) [ 38 ].…”
Section: Excitotoxicitymentioning
confidence: 99%
“…The administration of quetiapine at doses of 25 to 300 mg daily is well-tolerated and leads to significant reductions in aggression and irritability [3]. A number of drugs are known to cause SIADH [5]. Conventional antipsychotics and atypical psychotics can be associated with the development of the syndrome [11].…”
Section: Discussionmentioning
confidence: 99%
“…He had been given levetiracetam 3,000 mg a day due to a history of seizure and memantine 20 mg a day under the diagnosis of the major neruocognitive disorder due to TBI. A recent report examined memantine in patients with moderate TBI and concluded that memantine reduced serum levels of neuron-specific enolase, a marker of neuronal damage [5].…”
Section: Casementioning
confidence: 99%
“…An interesting study using acute administration of memantine and 17β-estradiol (E2) in rats subjected to FPI reported a reduction in degenerating neurons in hippocampus and cortex, albeit behavioral recovery was not robust enough in order to preferentially endorse this combination therapy ( Day et al, 2017 ). A recent report examined effects of memantine (2× daily for 7 days) in patients with moderate TBI and concluded that they benefited from this treatment as determined by significantly reduced serum levels of neuron-specific enolase, a marker of neuronal damage, as well as improvement in their Glasgow Coma Scale scores compared to the control group ( Mokhtari et al, 2018 ). Although animal findings overall supported the potential of NMDA antagonists as neuroprotective agents after TBI, many clinical studies have unfortunately been mostly inconclusive or terminated prematurely, such as those using selfotel, aptiganel, dexanabinol or EAA 494 ( Muir, 2006 ).…”
Section: Glutamate Receptors: a Gateway To Therapeuticsmentioning
confidence: 99%